Interchange rotation factors and player characteristics influence physical and technical performance in professional Australian Rules football. Issue 3 (March 2018) - Dillon, Patrick A.; Kempton, Thomas; Ryan, Samuel; Hocking, Joel; Coutts, Aaron J.
Abstract: Objectives: To examine the effects of match-related and individual player characteristics on activity profile and technical performance during rotations in professional Australian football. Design: Longitudinal observational study. Methods: Global positioning system data and player rating scores were collected from 33 professional Australian football players during 15 Australian football League matches. Player rating scores were time aligned with their relative total and high-speed running (HSR) distance (>20 km h −1 ) for each on ground rotation. Individual players' maximal aerobic running speed (MAS) was determined from a two-kilometre trial. A multilevel linear mixed model was used to examine the influence of rotations on physical activity profiles and skill execution during match play. Results: Rotation duration and accumulated distance resulted in a trivial-to-moderate reduction in relative total and HSR distances as well as relative rating points. The number of disposals in a rotation had a small positive effect on relative total and HSR distances and a large positive effect on relative rating points. MAS was associated with a moderate-to-large increase in relative total distance, but had a large negative effect on relative rating points. Previous rotation time, stoppages and the number of rotations in the quarter had a trivial-to-small negative effect on relative total and HSR distances. A greater speed (m min −1 ) was associated with a trivial increase in rating points during a rotation, while there was a trivial decrease in relative total distance as rating points increased. Conclusion: The complex relationship between factors that influence activity profile and technical performance during rotations in Australian football needs to be considered when interpreting match performance.